Psychology in action - Huffman, Karen. 4 0 16; 5 (Hoboken, N.J. : Wiley, 2005)
Contains a broad overview of the study of psychology, covering the historical development of the field, the brain and the mind, thinking and knowing, as well as topics on developmental, social, and abnormal psychology. Includes summaries of key points, definitions of terms, case studies, and biographies.
Spiral-bound.
Includes bibliographical references and indexes.
Adult;Adult.
Keywords: 2 -- 0; 6; Psychology;Psychology -- Textbooks.;Textbooks.; 20; 2